2009
DOI: 10.1523/jneurosci.0485-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Chemokine Receptor Activation in Transgenic Mice Reveals Peripheral Activation of CCR2 Receptors in States of Neuropathic Pain

Abstract: CCR2 chemokine receptor signaling has been implicated in the generation of diverse types of neuropathology, including neuropathic pain. For example, ccr2 knock-out mice are resistant to the establishment of neuropathic pain, and mice overexpressing its ligand, monocyte chemoattractant protein-1 (MCP1; also known as CCL2), show enhanced pain sensitivity. However, whether CCR2 receptor activation occurs in the central or peripheral nervous system in states of neuropathic pain has not been clear. We developed a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
143
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(154 citation statements)
references
References 54 publications
7
143
2
Order By: Relevance
“…It is interesting to note that the source of MCP-1 in these experiments appears to be the DRG neurons themselves. This up-regulated expression of both MCP-1 and CCR2 by DRG neurons is consistent with our previous findings (30,34) in other models of chronic pain, and suggests that CCR2 signaling within the DRG may play an important role in the genesis of nociceptor hyperexcitability.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is interesting to note that the source of MCP-1 in these experiments appears to be the DRG neurons themselves. This up-regulated expression of both MCP-1 and CCR2 by DRG neurons is consistent with our previous findings (30,34) in other models of chronic pain, and suggests that CCR2 signaling within the DRG may play an important role in the genesis of nociceptor hyperexcitability.…”
Section: Discussionsupporting
confidence: 92%
“…This process has been demonstrated on cultured (18) and previously injured adult DRG sensory neurons (27,(29)(30)(31)(32). In addition, chemokines are of central importance in the recruitment of leukocytes.…”
Section: Discussionmentioning
confidence: 83%
“…To identify CCL2-expressing cells in the brain, CCL2::RFP transcriptional reporter mice were subjected to saline solution or KA (30 mg/kg) to induce SE and killed 1 or 3 d later. Use of this transcriptional reporter line allows for intracellular labeling and identification of cells expressing Ccl2 mRNA (31). Notably, there was little staining for CCL2::RFP in the hippocampus of saline solution-treated mice.…”
Section: Resultsmentioning
confidence: 99%
“…CCL2::mRFP transcriptional reporter mice express mRFP from the CCL2 promoter. The reporter gene was introduced into the mouse genome by using bacterial artificial chromosome technologies (31). Female CCL2::mRFP mice maintained on the Jackson Laboratory B6 background were bred to inbred FVB mice to generate F1 hybrid B6.FVB-CCL2::mRFP.…”
Section: Methodsmentioning
confidence: 99%
“…However, the effect was more potent in MCP1 -/-mice than in wild-type mice. It has been shown that MCP1 binds to and reduces membrane 1491 Truncated MCP1 disrupts the blood-brain barrier CCR2 levels (probably through endocytosis) (Jung et al, 2009;Yao and Tsirka, 2010). The dramatic change observed in MCP1 -/-mice could be due to higher membrane CCR2 density, as in the absence of MCP1 there would be no recycling of CCR2 off the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%